Historical outline on the treatment of patients with chronic posttraumatic instability of shoulder joint (review of literature) - V. V. Monastyrev; V. Yu. Vasilyev; Puseva; N. V. Tishkov (Acta Biomedica Scientifica, 2013)
Systematic analysis of literature concerning treatment of patient with chronic posttraumatic instability of shoulder joint in historical aspect was realized. Main tendencies of development of surgical orthopedics including evolution of both palliative and. reconstructive surgical methods for shoulder joint were revealed. On the basis of more than 50 literature sources we managed to estimate progress of scientific researches from the point of view of evidence-based medicine. By the end of 1980s main directions in correction of described nosology which were determined by the level of device-dependent visualization were formed. Necessity of brand new change in mini-invasive surgery of deep and chronic injuries of shoulder joint structures according to the literary data caused, future creation of a new direction based on advanced extended data of pathogenesis of shoulder joint instability.